INNOVATIVE EFFORT AND LEARNIG PROCESSO OF THE POST-HARVEST MECHANICAL METAL INDUSTRY FROM PANAMBIanambi (Gestão & Regionalidade, 2021)
This paper analyzes the post-harvest mechanical metal industry's learning and innovation processes (in Panambi - RS). Brazilian industrialization favored the formation of productive capacity, to the detriment of fostering innovative capacity. However, innovation processes enhance companies and nations' development, especially in a competitive environment that requires competencies, constant learning, and the ability to innovate. It is an exploratory study of industrial companies, using a non-probabilistic sample questionnaire, with questions adapted from the REDESIST's questionnaire. The results point that there are: a local productive and innovative system; division of labor and productive specializations; technological and organizational training effort; local relations; benefits of proximity; and territorial organization. Innovative efforts are incremental and imitative. There is significant cooperation between companies, involving support institutions, which demonstrates synergies between them, capable of densifying the production system, promoting a virtuous development circle.
Keywords: technological innovations; learning processes; metal mechanics industry